SISTEM PENDUKUNG KEPUTUSAN PENENTUAN JURUSAN PADA SMK NU UNGARAN MENGGUNAKAN METODE NAIVE BAYES CLASSIFIER - Imam, Chalabi; Zuly, Budiarso (Information Technology and Telematics, 2018)
Abstract- SMK NU Ungaran is a vocational high school that has a majors program. Majors in SMK NU Ungaran are conducted so that students can channel their talents and interests and abilities in the department of SMK NU Ungaran, so that students can develop their potential. The selection of a major in the NU Ungaran Vocational School will determine a student's success. Therefore, if it is not appropriate in choosing a major opportunity that is very good for students will be lost, then the school must be able to facilitate students in accordance with their abilities so that students are aligned to the right majors by using data mining. The system development method used in this research is Waterfall which consists of requirement definition, system and software design using UML and implementation using PHP and MySQL.The final result of this study is the classification of the majors in NU Ungaran Vocational School by using the Naive Bayes Classifier algorithm can be used for the selection of appropriate majors and the results of the classification of the majors of NU Ungaran Vocational School using the Naive Bayes Classifier method that is TKJ majors at 20%, majoring in Graphic at 50%, majoring in Electronics at 23.3%, majoring in Automotive at 6.7%